2020
DOI: 10.3389/fimmu.2020.01633
|View full text |Cite
|
Sign up to set email alerts
|

Re-education of the Tumor Microenvironment With Targeted Therapies and Immunotherapies

Abstract: The clinical success of cancer immunotherapies targeting PD-1 and CTLA-4 has ignited a substantial research effort to improve our understanding of tumor immunity. Recent studies have revealed that the immune contexture of a tumor influences therapeutic response and survival benefit for cancer patients. Identifying treatment modalities that limit immunosuppression, relieve T cell exhaustion, and potentiate effector functions in the tumor microenvironment (TME) is of much interest. In particular, combinatorial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 180 publications
(222 reference statements)
0
37
0
Order By: Relevance
“…However, TAMs are highly plastic and heterogeneous in solid tumor ( Ngiow and Young, 2020 ). Generally, Th1 cytokines such as lipopolysaccharide (LPS), interferon-γ (IFN-γ), and tumor necrosis factor-α induce macrophages into a M1-like phenotype, playing a role in antitumor inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, TAMs are highly plastic and heterogeneous in solid tumor ( Ngiow and Young, 2020 ). Generally, Th1 cytokines such as lipopolysaccharide (LPS), interferon-γ (IFN-γ), and tumor necrosis factor-α induce macrophages into a M1-like phenotype, playing a role in antitumor inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also becoming increasingly clear that CD8 T cell-binding of neoantigens is insufficient for mounting a powerful antitumor response, and immunotherapy-induced antitumor responses require the added presence of CD4 T cells ( Kennedy and Celis, 2008 ). Multiple studies have indicated that CD4 T cells mediate antitumor effects through mechanisms that vary according to tumor microenvironments ( Ngiow and Young, 2020 ). In some settings, CD4 T cells became cytotoxic in the presence of IL-2, or in the absence of regulatory T cells ( Zuazo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The refining of molecular cells and immune regulation of therapeutic targets is increasing in the TME, and the clinical application also is growing more and more widely, for example, that resistance to PD-1/PD-L1 plays multiple roles in tumor immunotherapy, however, the test of limited activity PD-1 of resisting tumor types may have a good therapeutic effect in the strategy of reshaping the tumor inert environment in the future. Namely the possibility of immunotoxicity and immunotherapy to enhance antitumor immunity, in other words, use reasonable and selective combined immunotherapy in a limited TME to reactivate the anti-tumor immune response ( 185 ).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%